Basic algebra

Solve the equation:
3(-2x+1)=-5(x+1)

  1. 👍 0
  2. 👎 0
  3. 👁 24
  1. I did the last two for you. Now it's your turn.

    I'll be glad to check your answer.

Respond to this Question

First Name

Your Response

Similar Questions

  1. ALGEBRA 1!PLZ HELP!

    Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve the first equation for y. y = 2x-5 Substitute that for y in the second equation and solve for x. Then use the value of x to substitute back

    asked by SANDRO! on November 6, 2006
  2. Algebra

    I have some problems that I am having trouble with and I have some that need checking please. Thanks! Solve the equation. 4. (x+7/4)=2(x-1/6) Find all the value(s) of x that make thedenominator(s) zero. Then solve the equation. 6.

    asked by Soly on August 21, 2007
  3. MATH

    I NEED TO SOLVE FOR Y AND X im getting rele confused on this. ok here is the prob. x+y=5 x-2y=-4 equation 1 x+y=5 equation 2 x-2y=-4 Multiply equation 1 by -1. Add equation 1 to equation 2. The x term cancels. Solve for y. THEN,

    asked by Tony on December 17, 2006
  4. Math

    Solve the system by addition or substitution. 3x – 4y = 8 6x – 2y = 10 Please get me on the correct track for 3x -4y =8 x=4, y=1 for 6x - 2y =10 x= 2, y= 1 Solve one equation for x. 3x = 4y + 8 x = (4y + 8)/3 Insert that value

    asked by Amanda on May 20, 2007
  5. Algebra 1

    What is an equation of a line perpendicular to the line with equation y = 1 - 3x a.y=-3x + 5 b. y=3x + 5 c.y=-1/3x + 5 d. y=1/3x + 5 To solve the linear system below, which substitution of unkowns is proper ? x + 4y= -6 5x - 3y =

    asked by Ley on April 22, 2013
  6. Math

    1. Solve the equation. -6g = 42 a. g = 7 b. g = -7 c. g = 252 d. g = -252 2. Solve the equation. x/8 = 16 a. x = 128 b. x = 24 c. x = 8 d. x = 2 3. Solve the equation. 12m = 14.4 a. m = 120 b. m = 12 c. m = 1.2 d. m = 0.12 4.

    asked by Malasia on September 1, 2015
  7. math

    determine the equation of the line in y=mx+b form that passes through 1. (-8,1) & (-9, 2) 2. (3,7) & (-5, 9) 3, (-4,0) & (4,6) Part B ) For each equation Rewreite the y=mx+b equation in general form Ax+by+c=0 where A is positive b

    asked by thomas on February 8, 2007
  8. Substitution Method-Plz help

    Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get

    asked by Svetlana on October 17, 2006
  9. Math

    I need help with these three problems. They are on a Study Guide and I need some refreshing up of how to do them. 17. Solve the equation using the zero product property... -8n(5n+3) 19. Solve the equation by factoring 5z^2-2z-3=0

    asked by Amy on May 27, 2009
  10. math

    I need help with these three problems. They are on a Study Guide and I need some refreshing up of how to do them. 17. Solve the equation using the zero product property... -8n(5n+3) 19. Solve the equation by factoring 5z^2-2z-3=0

    asked by Amy on May 26, 2009
  11. Math

    I need help with these three problems. They are on a Study Guide and I need some refreshing up of how to do them. 17. Solve the equation using the zero product property... -8n(5n+3) 19. Solve the equation by factoring 5z^2-2z-3=0

    asked by Amy on May 26, 2009

More Similar Questions